HEC-RAS hydraulic model for floodplain area in Sembrong river - Marimin, Nor Azimah; Mohammad Razi, Mohd Adib; Ahmad, Mustaffa Anjang; Adnan, Mohd Shalahuddin; Rahmat, Siti Nazahiyah (Penerbit UTHM, 2018)
The study of floodplain is significant to human life and social economy. It can be seen that by using most computer models, locations of structures affected by floodwaters, such as bridges and roads cannot be effectively compared to the floodplain location in stream floodplain analysis. The purpose of this study is to develop an output of Hydrologic Engineering Center’s River Analysis System (HEC-RAS) hydraulic model and to enable one dimensional steady flow analysis. This study is applied to Sembrong river catchment area, located in Batu Pahat. Floodplain data features such as length of streams, bank position, streamline and cross-sections were used to produce river flow and its cross-sectional shape for each station along the study area. Total of 7 flow rate values were used to indicate an increase in the water level in order to accommodate the additional amount of water that flow into river. The results show that water will overflow into the floodplain at maximum flow rate of 24 m3 /s. The hydraulic model had indicated that 33 out of 65 stations were unable to accommodate the maximum flow rate and thus will led to flooding. By developing the hydraulic model, it clearly shows that the results are more reliable and the affected area can be easily identified. The developed flood model can be a very useful tool in flood management of Sembrong river in terms of river development planning, flood mitigation measures, flood evacuation planning and addressing public awareness. This study proved that HEC-RAS is one of effective instrument for analysis and modeling.